Substantial Aspects of Balance in Patients with Diabetic Neuropathy: A Physical Therapist’s Perspective - Ilona Gracie De Souza P.T.A, Rathish Manickam P.T.; Noronha P.T., Thrishala (International Journal of Innovative Research in Medical Science, 2017)
INTRODUCTION DIABETIC NEUROPATHY Diabetic neuropathy is defined as the presence of symptoms and or signs of peripheral nerve dysfunction in people with diabetes after the exclusion of other causes. The neuropathic disorder includes manifestations in the somatic and or autonomic parts of the peripheral nervous system.1